PENERAPAN ERGONOMI PADA RUANG FILLING REKAM MEDIS DI KANJURUHAN KABUPATEN MALANG - Ali Hanafiah; Nursela Maharani; Adi Santosa (JRMIK, 2023)
Background: Ergonomics is a science and technology, which1 seeks to harmonize1 methods, tools and the workenvironment to human abilities, so that1 humans can work optimally without the bad influence of their work inbalancing all facilities1 used both in activities and rest with human abilities both physically. as well as mentallyso as to make the overall quality of life better, from the demands of the task, work capacity from an ergonomicangle must always be in balance to achieve high work performance.Objective : This research was conducted at Kanjuruhan Hospital, Malang1 Regency. The purpose of this studywas to determine the application of ergonomics in the medical record filling room, to determine the supportingand inhibiting factors for the application of ergonomics to the filling room. Based on the existing ergonomicsKanjuruhan Hospital, Malang Regency. This type of research is descriptive research.Methods : The object of this research is objects that are in the medical record storage area such as lighting,completeness of work equipment, room temperature. Data collection techniques are documentation, directobservation, measurement. The data analysis used is descriptive data analysis.Results : The result of this study is that the application of ergonomics in the filling room has not been carriedout, the supporting and inhibiting factors can also affect the application of ergonomics if not addressedimmediately.Conclusion : This greatly affects the work performance of officers and the comfort in the storage area.Keywords : Ergonomic, Filling Room, Medical Records, Hospital